Assessing risk from invasive alien plants in China: Reconstructing invasion history and estimating distribution patterns of Lolium temulentum and Aegilops tauschii - Yang, Ming; Zhao, Haoxiang; Xian, Xiaoqing; Wang, Rui; Yang, Nianwan; Chen, Li; Liu, Wan-xue (Frontiers in Plant Science, 2023)
The establishment of invasive alien plants (IAPs) is primarily driven by climate warming and human activities, and their populations have a negative impact on agricultural economics, ecological systems, and human health. Lolium temulentum and Aegilops tauschii are critical IAPs in China because they reduce the quality of cereal grains and decrease wheat yields. Lolium temulentum is a winter-temperate weed that spreads easily and is poisonous to humans and animals. Aegilops tauschii is resistant to herbicides, has a high reproductive rate, and frequently grows in wheat. Both species have been listed in the Ministry of Agriculture and Rural Affairs of the People’s Republic of China’s management catalog since 2006. In the present study, the historical occurrence and invasion of each species were collected and reconstructed, which showed that the population outbreak of L. temulentum began in 2010, whereas that of A. tauschii began in 2000. Using the optimal MaxEnt model, the geographical distributions of L. temulentum and A. tauschii were predicted based on screened species occurrences and environmental variables under the current and three future scenarios in the 2030s and 2050s (i.e., SSP1-2.6, SSP2-4.5, and SSP5-8.5). The mean AUC values were 0.864 and 0.931 for L. temulentum and A. tauschii, respectively. Human influence index (HII), mean temperature of coldest quarter (bio11), and precipitation of coldest quarter (bio19) were the most significant variables for L. temulentum, whereas Human influence index, temperature seasonality (standard deviation×100) (bio4), and annual mean temperature (bio1) were the critical environmental variables for A. tauschi. Suitable habitat areas in China for L. temulentum and A. tauschii currently covered total areas of 125 × 104 and 235 × 104 km2, respectively. Future suitable areas of L. temulentum reached the maximum under SSP2-4.5, from 2021 to 2060, whereas for A. tauschii they reached the maximum under SSP5-8.5, from 2021 to 2060. Furthermore, the overlap area under the current climate conditions for L. temulentum and A. tauschii was approximately 90 × 104 km2, mainly located in Hubei, Anhui, Jiangsu, Shandong, Henan, Shaanxi, Shanxi, and Hebei.